Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jand.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

School Breakfast Policy Is Associated with Dietary Intake of Fourth- and Fifth-Grade Students

Abstract: No evidence was found to support discontinuation of breakfast in the classroom policy on the basis of concerns that children will eat excess calories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
(35 reference statements)
1
33
0
Order By: Relevance
“…11,20,21 There has been some concern around innovative school breakfast models such as BIC leading to an increase in the number of students eating more than one breakfast and contributing to an increased energy consumption and weight gain, 22,23 however multiple studies have found this not to be a concern. 17,24,25 Many prior studies looking at offering breakfast free to all students and breakfast serving models have focused on a limited number of schools and geographic areas. They also typically focused on only one serving model and/or school level (elementary, middle, or high).…”
Section: Introductionmentioning
confidence: 99%
“…11,20,21 There has been some concern around innovative school breakfast models such as BIC leading to an increase in the number of students eating more than one breakfast and contributing to an increased energy consumption and weight gain, 22,23 however multiple studies have found this not to be a concern. 17,24,25 Many prior studies looking at offering breakfast free to all students and breakfast serving models have focused on a limited number of schools and geographic areas. They also typically focused on only one serving model and/or school level (elementary, middle, or high).…”
Section: Introductionmentioning
confidence: 99%
“…However, because parents lack first-hand knowledge of their children’s intake at school, elementary school children must often self-report this information. For many years, elementary school children have provided dietary recalls for studies (Burghardt, Ensor, Hutchinson, Weiss, & Spencer, 1993; Fenton et al, 2015; Field et al, 1999; Moore et al, 2008; Ollberding et al, 2015; Ritchie et al, 2016; US Department of Agriculture, 2007; Wolfe & Campbell, 1993; Yuan et al, 2013) and interventions (Baranowski et al, 2003; Bartlett et al, 2013; Kitzman-Ulrich et al, 2011; Lindholm, Touliatos, & Wenberg, 1984; Luepker et al, 1996; McDonald, Brun, & Esserman, 1981; Receveur, Morou, Gray-Donald, & Macaulay, 2008; Reynolds et al, 2000; Wilson et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…This study cannot rule out the possibility that some students ate multiple breakfasts in a single day . While this is potentially worrisome, one study among younger students has suggested that school breakfast programs can improve diet quality and do not contribute to excess calories even despite the fact that some students ate multiple breakfasts . Indeed, other analyses in the Project BreakFAST study, students did not increase their caloric intake from baseline to follow‐up…”
Section: Discussionmentioning
confidence: 85%